Intracranial gliomas - Chernov, Mikhail F.; Muragaki, Yoshihiro; Kesari, Santosh; McCutcheon, Ian E. (Progress in neurological surgery / series editor L. Dade Lunsford, 2018)
Aggressive surgical removal is generally considered the main initial management option for most intracranial gliomas. It often results in resolution or alleviation of neurological symptoms and signs, normalizes intracranial pressure, facilitates characterization of the neoplasm, creates optimal conditions for adjuvant therapy and neurorehabilitation, and leads to prolongation of progression-free and overall survival of patients. Leading experts in neurosurgical oncology have contributed to this volume, highlighting modern principles of surgery for both newly-diagnosed and recurrent intracranial gliomas in adult as well as pediatric patients. The first of a three-volume set, it details epidemiological aspects, defines the importance of preoperative imaging, and describes current perioperative adjuvant needs. In addition, contemporary methods of intraoperative neurophysiological monitoring, the value of brain mapping for functional preservation, tips to prevent complications, and postoperative results are presented and discussed. This book and its accompanying volumes are mainly directed at neurosurgeons, neuro-oncologists and other clinicians treating patients with brain tumors.